2011
DOI: 10.1002/chem.201003133
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Trace Heavy‐Metal Ions by Filtration on Sol–Gel Membrane Arrays

Abstract: The increasing concern for environmental pollution, especially the impact of heavy metals (e.g., Hg, Pb, As, Cd, and Ag), has stimulated active investigations.[1] These heavy metals arise mainly from industrial wastewater and exist in cationic forms. They are absorbed by fish or shellfish and accumulated millions of times even at very low concentrations. Once these heavy-metal ions enter the human food chain they cannot be degraded and are extremely harmful to our health. They can cause serious damage (e.g., i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 63 publications
0
34
0
Order By: Relevance
“…Scanner imaging has been developed for decades and has proved a handy tool for digitizing images. [29][30][31][32][33][34] After centrifuging, four quartz tubes (inside diameter ¼ 1.7 mm, outside diameter ¼ 2.5 mm, length ¼ 4 cm) were utilized to siphon around 10 mL supernatant liquid of each sample. The digital image of this RIDA array was acquired subsequently, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Scanner imaging has been developed for decades and has proved a handy tool for digitizing images. [29][30][31][32][33][34] After centrifuging, four quartz tubes (inside diameter ¼ 1.7 mm, outside diameter ¼ 2.5 mm, length ¼ 4 cm) were utilized to siphon around 10 mL supernatant liquid of each sample. The digital image of this RIDA array was acquired subsequently, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3, the colorimetric response was saturated even at 200 mL of water sample at concentration of 50 nM, while the relationship between colorimetric response and sample volume of 25 nM kept linear up to 200 mL. Therefore, the sample volume should be adjusted depending on the desired detection range of Hg B thiolactone [34,35]. In alkaline solutions, metal hydroxide species (soluble M(OH) + and/or insoluble precipitate of M(OH) n )…”
Section: The Volume Of Water Samplesmentioning
confidence: 99%
“…Fluorometric sensor arrays hold promise to be such a technique [18,19]. Various sensor arrays for heavy-metal-ion detection using commercial or custom fluorescent indicators have been reported that manifest remarkable selectivity at mM concentrations of the ions.…”
Section: Introductionmentioning
confidence: 99%